Consumption of musical content and movies/series online in Portugal - Silva, A.; Trindade, G.; Santos, M-C. (Consumption of musical content and movies/series online in Portugal, 2018)
This study addresses the consumption of musical and/or movies and series online according to the frequency of Internet use. The time spent on Internet, nowadays, goes beyond a simple search or checking the email. What will be the sociodemographic characteristics of Portuguese users? Will the choices facing the Portuguese users be homogeneous in what concerns the frequency of Internet use to access music and movies online? The answer to these research questions is the aim of this study. Using the Flash Eurobarometer 437 database, it is identified that age is significantly related to the frequency of using the Internet to access music and movies online. It is also observed that gender is significantly related to frequency of using the Internet to access movies online. However, the perception of quality and speed of Internet connection are not significantly related to frequency of using the Internet. The choices facing the Portuguese users are not homogeneous regarding the frequency of Internet use to access music and movies online as observed in four different clusters with different characteristics. These results can be an indication that policies concerning the music and movies contents should fit the characteristics of each of these clusters.